Virtual Tour Campus Sebagai Media Promosi di Masa Pandemik Covid-19 - Lita Karlitasari; Boldson Herdianto Situmorang; Agung Prajuhana Putra; Amalia Sabrina; Diva Randika (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2022)
The use of Virtual Tours is now widely used to introduce infrastructure facilities owned by a campus. For almost a year, the COVID-19 pandemic has made prospective students and college students hesitant to continue their studies. This raises concerns if you come directly to campus to see all the facilities in it. The purpose of this research is to create a virtual campus tour application as an alternative media promotion during the COVID-19 pandemic. This study uses the Multimedia Development Life Cycle (MDLC) method using augmented reality. The result of this research is an application in the form of a virtual game, where before exploring the study programs, the user will be asked to have the appropriate character, then with the help of controlling the joystick from the keyboard, the user can enter the rooms and the information in it, either in the form of direct templates. or use the barcode to go directly to the information in it. Thus, in addition to users becoming more familiar with the Computer Science Study Program environment and the infrastructure in it, it is also an inspirational tool, that to study or create applications it can be done if you enter as a student.